2010
DOI: 10.1111/j.1524-4725.2010.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Effectiveness, and Subjective Experience with Topical Bimatoprost 0.03% for Eyelash Growth

Abstract: Bimatoprost was found safe for eyelid application and was associated with enhanced eyelash growth. All subjects noticed favorable changes in the appearance of their eyelashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
(35 reference statements)
0
41
0
Order By: Relevance
“…6,9 Recently, the effects of bimatoprost 0.03% on eyelash growth when applied topically to the skin of the eyelid margins were evaluated in an open-label study that found bimatoprost 0.03% to be safe and associated with longer, thicker, and darker eyelashes. 10 The current study aimed to evaluate the safety and efficacy of once-daily administration of bimatoprost 0.03% or vehicle to the upper eyelid margins.…”
mentioning
confidence: 99%
“…6,9 Recently, the effects of bimatoprost 0.03% on eyelash growth when applied topically to the skin of the eyelid margins were evaluated in an open-label study that found bimatoprost 0.03% to be safe and associated with longer, thicker, and darker eyelashes. 10 The current study aimed to evaluate the safety and efficacy of once-daily administration of bimatoprost 0.03% or vehicle to the upper eyelid margins.…”
mentioning
confidence: 99%
“…This outcome was confirmed in case studies and in a formal proof-of-concept study, with bimatoprost 0.03% ophthalmic solution applied daily to the upper eyelashes [5,6,7]. In the pivotal study conducted in the United States in 278 healthy subjects, a statistically significant improvement from baseline in eyelash prominence was demonstrated in the bimatoprost 0.03% group versus the vehicle control group, based on the validated physician's Global Eyelash Assessment (GEA) scale [7,8]. Statistically significant increases in eyelash length, thickness and darkness were also observed in the bimatoprost 0.03% group versus the control [8].…”
Section: Introductionmentioning
confidence: 55%
“…During the pre-registration studies of bimatoprost 0.03% in glaucoma, eyelash growth was frequently documented as an adverse event (AE) [2,3,4]. This outcome was confirmed in case studies and in a formal proof-of-concept study, with bimatoprost 0.03% ophthalmic solution applied daily to the upper eyelashes [5,6,7]. In the pivotal study conducted in the United States in 278 healthy subjects, a statistically significant improvement from baseline in eyelash prominence was demonstrated in the bimatoprost 0.03% group versus the vehicle control group, based on the validated physician's Global Eyelash Assessment (GEA) scale [7,8].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…79 Its safety, efficacy, and tolerability are well documented. 80,81 The successful use of bimatoprost for eyelash enhancement has led to its off-label use to treat eyebrows and, in the experience of the authors, is something often initiated by the patient with successful results. Although not FDA-approved for this purpose, a recent publication seems to support the use of bimatoprost ophthalmic solution 0.03% for eyebrow growth.…”
Section: Eyelashes and Eyebrowsmentioning
confidence: 95%